A superconducting manifold‐coupled triplexer with an iterative design method at X‐band. Issue 12 (22nd September 2016) - Song, Xiaoke; Liu, Yong; Wei, Bin; She, Yajun; Wang, Honghua; Luo, Tao; Cao, Bisong; Lu, Xinxiang; Jiang, Ying
ABSTRACT: This paper presents a superconducting manifold‐coupled narrowband triplexer at X‐band frequency. The high Q ‐value resonator is adopted to create a filter with low insertion loss. Impedance matching and iterative design methods are used to design the duplexer and manifold structure. Furthermore, metal shielding plates are used to separate the three channels to suppress the box resonant modes. The three bandwidths of the superconducting triplexer are all 60 MHz, and the center frequencies are 9.0, 9.12, and 9.24 GHz. The triplexer exhibits good performance at 65 K, with an insertion loss of 0.7 dB at 9.24 GHz. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2949–2954, 2016